Fluid power dynamics - Mobley, R. Keith, 1943- (Plant Engineering Maintenance.)
Fluid Power Dynamics is a 12-chapter book in two sections covering the basics of fluid power through hydraulic system components and troubleshooting. The second section covers pneumatics from basics through to troubleshooting. This is the latest book in a new series published by Butterworth-Heinemann in association with PLANT ENGINEERING magazine. PLANT ENGINEERING fills a unique information need for the men and women who operate and maintain industrial plants: It bridges the information gap between engineering education and practical application. As technology advances at increasingly faster.